2007
DOI: 10.1038/nchembio.2007.34
|View full text |Cite
|
Sign up to set email alerts
|

ATP-competitive inhibitors of the mitotic kinesin KSP that function via an allosteric mechanism

Abstract: The mitotic kinesin KSP (kinesin spindle protein, or Eg5) has an essential role in centrosome separation and formation of the bipolar mitotic spindle. Its exclusive involvement in the mitotic spindle of proliferating cells presents an opportunity for developing new anticancer agents with reduced side effects relative to antimitotics that target tubulin. Ispinesib is an allosteric small-molecule KSP inhibitor in phase 2 clinical trials. Mutations that attenuate ispinesib binding to KSP have been identified, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
106
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(119 citation statements)
references
References 26 publications
12
106
0
1
Order By: Relevance
“…The ability to confer drug resistance by introducing mutations in the induced fit binding pocket of Eg5 raises the possibility that such mutations may be encountered in tumors during chemotherapy if Eg5 inhibitors were to enter the clinic. In support of our results it has been reported that Ispinesib-resistant cancerous cells were found to harbor a D130V substitution located in loop L5 of Eg5 [46]. …”
Section: Monastrol and Stlc Have Been Characterized As Eg5 Specific Isupporting
confidence: 92%
“…The ability to confer drug resistance by introducing mutations in the induced fit binding pocket of Eg5 raises the possibility that such mutations may be encountered in tumors during chemotherapy if Eg5 inhibitors were to enter the clinic. In support of our results it has been reported that Ispinesib-resistant cancerous cells were found to harbor a D130V substitution located in loop L5 of Eg5 [46]. …”
Section: Monastrol and Stlc Have Been Characterized As Eg5 Specific Isupporting
confidence: 92%
“…Only the E116R and D130K motor proteins displayed differing levels of inhibition between the two compounds used, the former being more sensitive to monastrol and the latter to STC. Of the C-terminal L5 mutants, D130V (open blue triangles) and A133D (filled red triangles) were the most insensitive to either inhibitor, as anticipated from studies on ispinesib (16). For the N-terminal L5 substitutions, loss of allosteric compound sensitivity was more marked in samples with aliphatic residue substitutions at position 116, compared with Eg5 proteins with charged residues at these positions.…”
Section: Preservation Of N-terminal Local Structure and C-terminal Chmentioning
confidence: 82%
“…1B). However, we note that the E116V and E118N substitutions are present in the Drosophila Kinesin-5 protein that is insensitive to allosteric inhibitors and that the D130V and A133D mutations were found in human cell lines resistant to Eg5 allosteric inhibitors (16).…”
Section: Substitutions Of L5 Residues Results In Altered Sds-pagementioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, a distinct, but related, effect has recently been described in a mutant of the mitotic kinesin KSP (also called Eg5). The KSP mutant was discovered in a laboratory screen and confers drug resistance by an allosteric mechanism involving enhanced affinity for ATP (33).…”
Section: Discussionmentioning
confidence: 99%